Can yoga be used to treat gastroesophageal reflux disease? - Kaswala, Dharmesh (Medknow Publications & Media Pvt Ltd, 2013)
Yoga methods including Pranayama are the best ways to prevent many diseases and their progression. Even though, Yoga is widely practiced, its effects on certain medical conditions have not been studied or reported. Gastroesophageal reflux disease (GERD) is one of them. GERD is extremely common condition requiring frequent consumption of over-the-counter or prescribed proton pump inhibitors (PPI). In severe symptoms of GERD and in the presence of multiple etiologies, PPIs are insufficient to relieve the symptoms of gastric reflux. Regular and proper use of the Yoga along with PPI can control the severe symptoms of GERD and can avoid or delay the necessity of invasive procedures. This evidence-based case report focuses on the effects of Yoga on GERD. Our case report showed that regular practice of Kapalbhati and Agnisar kriya along with PPI, patients with hiatal hernia had improvement in severe symptoms of GERD, which were initially refractory to PPI alone.